Site conditions and vegetation determine phosphorus and sulfur speciation in soils of Antarctica. (1st February 2019) - Prietzel, Jörg; Prater, Isabel; Colocho Hurtarte, Luis Carlos; Hrbáček, Filip; Klysubun, Wantana; Mueller, Carsten W.
Abstract: Phosphorus (P) and sulfur (S) are essential elements for life, and peculiarities of Antarctic soils regarding their S and P status likely affect terrestrial and aquatic ecosystems in Antarctica. Current climate warming is accompanied by deglaciation, increased availability of water, and vegetation establishment in many regions of Antarctica. The effect of these changes on soil P and S availability, ecosystem succession, mineral weathering, and important processes of soil formation and geochemistry ( e.g. organic carbon sequestration, formation of secondary minerals) are largely unknown. Detailed knowledge on different P and S pools in soils of Antarctica is required for sound predictions of climate warming effects on important (bio)geochemical processes. We quantified the P and S concentration and speciation for various Antarctic soils using synchrotron-based X-ray absorption near edge structure (XANES) spectroscopy and related the soil P and S status to important soil and site properties. The soils, which have mostly remained at an initial stage of pedogenesis, differed considerably with respect to their P and S status. The P stock of most soils was dominated by Ca-bound (apatite) P (60–70% of total P). Some soils showed a marked accumulation of either Al-bound P (up to 60% of total P), Fe-bound P (up to 57%), Na- and K-bound P (up to 37%), or organic P (up to 54%). The S speciation also differed considerably among soils. Similar to other terrestrial environments, we observed a transformation of lithogenic apatite P and sulfide S into Al- and Fe-bound phosphate and sulfate as well as organic S and P. The transformation proceeded much more slowly than in soils with temperate humid climate, reflecting the cold and arid climate as well as the absence of vascular plants. The different P and S status of the soils could be related to the following site factors: (i) Parent material – soils formed from basalt had larger contents of total P as well as Al- and Fe-bound P compared to soils formed from mixture of basalt and sandstone. (ii) Sea spray influence – An upland soil affected by eolian deposition of sea spray showed topsoil enrichment of alkali-bound P, Ca-bound P, and CaSO4 . (iii) Inundation by seawater – Soils inundated by seawater had higher total P and S concentrations and higher concentrations of inorganic sulfide than upland soils. (iv) Soil moisture – Soils with increased soil moisture or wet conditions showed increased concentrations of P bound to pedogenic Al and Fe minerals and smaller contributions of Ca-bound (apatite) P to total P than soils under permanently arid conditions. (v) Colonization by mosses – Moss establishment resulted in topsoil P depletion and transformation of apatite P into Al- and Fe-bound P, but also in topsoil S accumulation and conversion of sulfide S into organic S forms. According to our study, the ongoing climate warming in Antarctica at many places will likely change soil P and S speciation as well as P and S availability to terrestrial and aquatic ecosystems, thus altering key biogeochemical processes like mineral weathering, secondary mineral formation, and soil C sequestration.